2013
DOI: 10.1021/ja310849c
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Mesoporous Carbon Nanosheets and Their Derived Graphene Nanosheets: Synthesis and Efficient Lithium Ion Storage

Abstract: We report a new solution deposition method to synthesize an unprecedented type of two-dimensional ordered mesoporous carbon nanosheets via a controlled low-concentration monomicelle close-packing assembly approach. These obtained carbon nanosheets possess only one layer of ordered mesopores on the surface of a substrate, typically the inner walls of anodic aluminum oxide pore channels, and can be further converted into mesoporous graphene nanosheets by carbonization. The atomically flat graphene layers with me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
436
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 600 publications
(456 citation statements)
references
References 54 publications
19
436
1
Order By: Relevance
“…The P atoms bonded to the carbon are electrochemically active and can offer active sites for sodium sotrage. The electronic state of nanosheets was also changed by the heteroatoms doping, facilitating the adsorption of electrolyte ions 11, 14, 16…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The P atoms bonded to the carbon are electrochemically active and can offer active sites for sodium sotrage. The electronic state of nanosheets was also changed by the heteroatoms doping, facilitating the adsorption of electrolyte ions 11, 14, 16…”
Section: Resultsmentioning
confidence: 99%
“…Besides, heteroatoms doping has been also regarded as one of the most effective strategies to promote the electrochemical behaviors of carbon materials, owing to the tailoring of electronic properties and effects on electronic charge distribution of adjacent carbon atoms 13. In addition, 2D nanosheets often possess large exposed surfaces and specific facets, which can offer high active surface area for ions insertion, continuous conducting pathways for electrons, open shortened diffusion distance for ions and facile strain relaxation during battery operation, making them be ideal electrode materials for SIBs with high power and energy density 14. Nonetheless, producing high quality and large quantity of 2D nanomaterials, especially doped with heteroatoms, in a commercially viable way is still full of high challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the authors erroneously calculated the energy and power on a single electrode basis. Other materials such as bottom-up-synthesized graphene, [ 85 ] electrochemically exfoliated graphene, [ 86 ] holey-RGO hydrogel, [ 87 ] CVD-derived fl exible graphene paper, [ 88 ] polysulfi de-functionalized RGO [ 89 ] and catalytically exfoliated few-layer graphene [ 90 ] were characterized and tested. Unluckily, despite the valuable cycling performances observed in two cases, [ 89,90 ] none of them seemed to have the potential of meeting the requirements of practical use.…”
Section: Continuedmentioning
confidence: 99%
“…It was reported that, Brunauer-Emmett-Teller (BET) surface area decreases with increase in the GO ratio in the composite. In another case, the same hydrothermally driven low-concentration micelle assembly approach was used with the help of anodic aluminum oxide (AAO) membranes to provide a large surface area [33]. After the hydrothermal treatment, AAO membrane was carbonized at 400-500°C for 2 h in argon atmosphere, followed by further carbonization at 700°C for 2 h in the same environment.…”
Section: Soft-template Methodsmentioning
confidence: 99%